Evaluation of Tigris River Water Quality in Selected Sites within Baghdad City - Taleb Kadhum, Shaimaa (Iraqi Journal of Civil Engineering, 2016)
The present research focuses on the evaluation of the Tigris river water quality within the city of Baghdad. Thirty samples were collected monthly from ten sites (each site contains three positions center of river, Rasafa side, Karkh side) on the Tigris river within Baghdad city along one year (from Feb.2010 to Feb. 2011). Samples were analyzed for eleven water quality variables including physical, chemical, and biological parameters. The results showed increases in pH, TDS, TSS, Cl-1, SO4-2, and BOD values in some of the sites through study area, but all values remain within the allowable Iraqi and WHO limits except of SO4-2, it was exceeded the allowable limits in multiple sites.